2019
DOI: 10.3389/fcell.2019.00151
|View full text |Cite
|
Sign up to set email alerts
|

CCDC42 Localizes to Manchette, HTCA and Tail and Interacts With ODF1 and ODF2 in the Formation of the Male Germ Cell Cytoskeleton

Abstract: Terminal differentiation of male germ cells into functional spermatozoa requires shaping and condensation of the nucleus as well as the formation of sperm-specific structures. A transient microtubular structure, the manchette, is mandatory for sperm head shaping and the development of the connecting piece and the sperm tail. The connecting piece or head-to-tail coupling apparatus (HTCA) mediates the tight linkage of sperm head and tail causing decapitation and infertility when faulty. Using mice as the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…A similar distribution in the manchette and the sperm tail was observed for the outer dense fibre protein 1, ODF1 31 , posing the question whether the observed colocalization indicates interaction or interdependency. We, therefore, investigated CFAP52 localization in testicular sections using both wild-type as well as Odf1-deficient mice 28 .…”
Section: Cfpa52 Localizes To the Spermatid Manchette And To The Spermsupporting
confidence: 57%
See 1 more Smart Citation
“…A similar distribution in the manchette and the sperm tail was observed for the outer dense fibre protein 1, ODF1 31 , posing the question whether the observed colocalization indicates interaction or interdependency. We, therefore, investigated CFAP52 localization in testicular sections using both wild-type as well as Odf1-deficient mice 28 .…”
Section: Cfpa52 Localizes To the Spermatid Manchette And To The Spermsupporting
confidence: 57%
“…Hook1 -depletion, furthermore, disrupted the tight connection between flagellum and nucleus causing sperm decapitation 26 . Sperm decapitation and male infertility were also observed when the outer dense fibre protein ODF1 or one of its interacting proteins centrosomal protein coiled-coil domain containing 42 (CCDC42) or the testis-specific SUN-domain protein SPAG4L/SUN5 were mutated 28 31 . SUN-domain proteins are integral nuclear membrane proteins and are part of the linker of nucleoskeleton and cytoskeleton (LINC) complex responsible for bridging the nuclear envelope and the cytoskeleton 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Moretti et al suggested that TBL1XR1 interacts with SLY, which is closely associated with the master genes of spermatid transcriptional regulation and further modulated the chromatin remodelling process (Moretti et al., 2017). Contreras et al revealed that CCDC42 localises to spermatid manchette, and binds to the ODF1 and ODF2 proteins, which are required for the formation of cytoskeletal structures of sperm (Tapia Contreras & Hoyer‐Fender, 2019). Moreover, PRAME deletion in mice has been found to be associated with germ cell apoptosis and abnormal seminiferous tubules, suggesting its role in spermatogenesis (Lu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SPERM1 transports UBQLN1 [174] and RANBP17 [175] in the manchette. The coiled-coil domain containing 42 (CCDC42) protein has been found to be enriched in the perinuclear ring and to colocalize with acetylated-tubulin in the manchette [176]. Ccdc42-mutant mice display defects in the manchette [177].…”
Section: Intramanchette Transport (Imt)mentioning
confidence: 99%
“…Ccdc42-mutant mice display defects in the manchette [177]. The molecular function of CCDC42 is unknown, but it was shown to interact with ODF1 and ODF2 [176]. Table 4.…”
Section: Intramanchette Transport (Imt)mentioning
confidence: 99%